Behavior and Performance of Dairy Cows After Transfer from Tied to Cubicle Housing. Issue 1 (2nd January 2018) - Pavlenko, Anne; Lidfors, Lena; Arney, David R.; Kaart, Tanel; Aland, Andres
ABSTRACT: Behavior and performance changes when tied dairy cows were moved to a loose housing system in a cubicle system were investigated. Behavioral observations were made for 3 consecutive days in 3 periods after transition. The cows ( n  = 105) were observed on 18 sampling occasions for 1 month. Recordings were made of body positions and general and social behaviors. Monthly milk records were collected 1 year before and 1 year after transition. Cows walked more during the 1st observation period than during the other periods ( p  < .05). Walking activity also differed between days when nested to period ( p  < .05). During the 1st period, cows ruminated while standing more than during the 3rd period ( p  < .05). Cows ate and groomed less and vocalized more during the 1st period ( p  < .05). It was concluded that after transition from a tied to a cubicle system, several behaviors were affected during the 1st days, and milk production of multiparous cows was negatively affected, although this effect was not long-term.